CORYNEBACTERIUM: FEATURES OF THE STRUCTURE OF THE BACTERIAL CELL - G. G. Kharseeva; N. A. Voronina (Журнал микробиологии, эпидемиологии и иммунобиологии, 2017)
In a review of the features of the bacterial cells are Corynebacterium structure: characterized by an upper layer, highly organized cell wall, cytoplasmic membrane, cytoplasm, nucleoid. Described in detail the structure of the upper layer containing pili (fimbriae), microcapsule surface proteins - PS-2, DIP1281, 67-72r protein (hemagglutinin), porins, sialidase (neuraminidase). These components are the ability to initiate a serial of Corynebacterium work with the host cell, followed by colonization. It submitted a detailed description of the structure and functions of cell wall structures - cord factor, which is a second barrier permeability; arabinogalactan, peptidoglycan, lipomannan and lipoarabinomannan. The structure and function of the cytoplasmic membrane as the main diffusion barrier cell cytoplasm and the genome of Corynebacterium. Presented different molecular genetic methods for the identification and differentiation of closely related species of Corynebacterium.